Assessing moisture content in XLPE power cables using frequency-dependent tangent delta measurements - Babu Naik Gugulothu; Sanjay Lakshminarayanan; Madhu Palati; Suresh Haleyur Lakshmegowda; Mahipal Bukya (Materials Research Express)
The reliability of cross-linked polyethylene (XLPE)-insulated power cables, mostly used for electricity distribution and transmission in urban areas, is often compromised due to the lack of effective condition-based monitoring systems. This leads to difficulties in early fault detection and increased risk of unscheduled outages, and failures, particularly in cable end terminations. This research aims to develop a robust and accurate methodology for estimating moisture content in XLPE cable end terminations to enhance condition-based monitoring and ensure reliable power delivery. The study employed frequency domain spectroscopy to examine the dielectric properties of XLPE cable samples with varying moisture content levels. A novel predictive formula was derived to estimate moisture content using dielectric frequency response (DFR) supported by validation through sweep frequency response analysis (SFRA) tests. We conduct an experiment to estimate the moisture content and observe satisfactory agreement between the experimental and theoretical values. The proposed method achieved a high accuracy of 96%; the percentage error variation was minimal in moisture estimation, outperforming existing techniques. This study provides a practical and reliable approach for monitoring XLPE cable condition, particularly at end terminations. The proposed methodology ensures accurate moisture content estimation, enabling early fault detection and reducing the risk of unscheduled outages. This advancement has major implications for enhancing the reliability and efficiency of urban power systems.